2016
DOI: 10.2139/ssrn.2853339
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Sites, Individual Social Capital and Happiness

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 60 publications
1
25
0
1
Order By: Relevance
“…SNS have the potential to increase both the number and intensity of these connections, including the influence of family, friends and others (Chesley and Johnson : 590). SNS could also act as a substitute for face‐to‐face interaction among those who are socially isolated or lonely, characteristics closely linked with socio‐economic status and health, potentially enhancing their well‐being (Arampatzi, Burger and Novik ).…”
Section: Social Networking Sites Psycho‐social Impacts and Well‐beingmentioning
confidence: 99%
See 1 more Smart Citation
“…SNS have the potential to increase both the number and intensity of these connections, including the influence of family, friends and others (Chesley and Johnson : 590). SNS could also act as a substitute for face‐to‐face interaction among those who are socially isolated or lonely, characteristics closely linked with socio‐economic status and health, potentially enhancing their well‐being (Arampatzi, Burger and Novik ).…”
Section: Social Networking Sites Psycho‐social Impacts and Well‐beingmentioning
confidence: 99%
“…The accumulation of social capital – social resources that are available through social interactions (Bourdieu ) such as access to information, opportunities and support that might be otherwise unavailable (Putnam ) – is a common motivator of SNS use (Yoo and Jeong ). This is important as individual social capital has been shown to have a positive association with a range of subjective well‐being measures (Arampatzi et al : 100; Portela, Neira and del Mar Salinas‐Jiménez ). SNS platforms not only provide users with greater opportunity for gaining social support from their existing connections but also aid them in increasing their social spheres and the subsequent social capital that they can access (Ellison et al ; Joinson ; Valenzuela, Park and Kee ).…”
Section: Social Networking Sites Psycho‐social Impacts and Well‐beingmentioning
confidence: 99%
“…Research focusing on SWB underlines "the importance of studying dispositions in dynamic terms -that is, as a reaction to circumstances -rather than as static" (Reis, Sheldon, Gable, Roscoe, & Ryan, 2000, pp.431-432), suggesting that a diary method is particularly suitable for our context. Furthermore, with few exceptions (e.g., Kross, Verduyn, Demiralp, Park, Lee, Lin, Shablack, Jonides, & Ybarra, 2013;Arampatzi, Burger, & Novik, 2016;Burke & Kraut, 2016), research exploring the link between SNS participation and users' SWB has been dominated by crosssectional studies that focus on individual differences between study participants. However, the experience of using SNSs may differ from day to day; while on some days users may experience a high level of positive emotions following their SNS activities, on other days their perceptions may be different.…”
Section: Empirical Studymentioning
confidence: 99%
“…Additionally, we found that loneliness moderated the relationship between ICT use and social isolation. Prior research (Arampatzi, Burger, & Novik, 2016) has also found that loneliness moderated the relationship between ICT use and happiness. Although we do not consider happiness in our study, social isolation among the elderly represents a critical factor that influences the elderly's happiness, and loneliness moderates its relationship with ICT use.…”
Section: Discussion Of Findingsmentioning
confidence: 81%